Metal-Embedded SU-8 Slab Techniques for Low-Resistance Micromachined Inductors - Manot Mapato; Prapong Klysuban; Thanatchai Kulworawanichpong; Nimit Chomnawang (Institute of Advanced Engineering and Science, 2017)
This work presents new fabrication technique for micro power-inductors by using metal-embedded SU-8 slab techniques. This techniques used X-ray lithography to fabricate high aspect-ratio LIGA-like micro-structures in form of embedded structure in SU-8 slab and applied for inductor’s winding fabrication with aspect-ratio of 10. Thishigh-aspect ratiostructure can provide very low resistance winding but preserve small form factor and low profile. Inductors were designed as pot-core structures with8 μm-thick permalloy core and 250 μm-thick copper winding. 4-types of inductors were fabricated including 3, 5, 10 and 16 turns in the area of 1.8 mm2 to 9.5 mm2. All inductors have overall heights of 370 μm, measured inductance value in a range of 70 nH to 1.3 μH at 1 MHz and DC resistance value of 30 mΩ to 336 mΩ for 3 turns to 16 turns respectively. From this result, high aspect-ratio inductors show good results including low-resistance, high inductance, and a small form factor as expected.